Financing the Belt and Road Initiative (BRI): research agendas beyond the "debt-trap" discourse. Issue 2 (3rd March 2020) - Lai, Karen P. Y.; Lin, Shaun; Sidaway, James D.
ABSTRACT: By way of introduction to the four papers that follow, we chart some key parameters of debate about finance and the Belt and Road Initiative (BRI). In particular, we argue that the rise of discourses about "predatory lending" and "debt trap" (that feature in much commentary and reportage about BRI) merits critique and contextualization. The financing needs of BRI also raise important implications for the geography of financial markets and business services in Asia and other key locations in global financial networks. The networked nature of financial centers and the vital role of advanced business services bring into view actors, sites and spaces (such as law firms and offshore centers) that have been neglected by the geopolitical lenses most often applied to analyze BRI.